Praanggapan Dalam Film Pendek Tilik: Kajian Pragmatik - Asmaya Jutri, Fiony; Anggraini, Fia; Fathurrahman, Fathurrahman; Prihatin Syahroni, Irma (Alinea: Jurnal Bahasa, Sastra dan Pengajaran, 2025)
This study aims to examine the presuppositions in the speech of the characters in the short film Tilik by Bagus Martono, directed by Wahyu Agung Prasetyo. This short film is interesting to study because it depicts the daily communication practices of village communities that are full of gossip, social prejudice and stereotypes towards women. Presuppositions are an important part of pragmatic studies that contain shared knowledge between speakers and interlocutors. This study is relevant because presuppositions not only convey implicit meanings, but also reflect the values and social structures inherent in language. This study uses a qualitative descriptive method with a pragmatic approach. The data source is the speech of the characters in the film Tilik, which is obtained through the Listening method with note-taking techniques. This technique is carried out by intensively listening to the film, noting all utterances containing presuppositions and transcribing them. The data are analyzed based on the classification of presuppositions according to Yule's theory (2006), which divides them into six types, namely 1). Existential presuppositions, 2). Factual presuppositions, 3). Non-factual presuppositions, 4). Lexical presuppositions, 5). Structural presupposition, 6). Counterfactual presupposition. Data analysis was conducted through interactive analysis techniques according to Miles and Huberman which include data reduction, data presentation and data verification or conclusions. The results of the study showed that there were 92 presupposition data consisting of existential presuppositions (15 data), factive presuppositions (24 data), lexical presuppositions (1 data), structural presuppositions (42 data), nonfactive presuppositions (8 data), counterfactual presuppositions (2 data). These findings indicate that the presuppositions in the short film Tilik not only build implicit meanings in the dialogue, but also reflect the social values and communication dynamics of the village community.